ANALISIS DAN PENGEMBANGAN MATERI AJAR DALAM KURIKULUM PAI: ANALISIS DAN PENGEMBANGAN MATERI AJAR DALAM KURIKULUM PAI - Ilfah, Ade; Hrp, Ibnu Alwi Zarkasi; Halimah, Siti (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2024)
Abstract This research aims to analyze and develop teaching materials in the Islamic Religious Education (PAI) curriculum. In the learning process, open materials have an important role in helping teachers achieve educational goals. This research uses a qualitative method with a descriptive analytical approach. Data was collected through documentation studies and interviews with PAI teachers. The research results show that the material provided in the PAI curriculum needs to be adapted to current developments, student needs and local context. The development of teaching materials is carried out through the integration of character values, the use of technology and contextual approaches. This research recommends increasing teacher competence in developing and developing innovative and relevant teaching materials. Keywords: Curriculum of Islamic Education (PAI), Teaching Materials, Material Development, Islamic Religious Education, and Learning Innovation